Compatibilidade de óleos essenciais e Trichoderma sp. em antagonismo contra Fusarium sp - Mora, Érika Costa Bretones (Universidade Federal de São Carlos, 2026)
The olive tree (Olea europaea L.) was introduced into Brazil more than two centuries ago and faces phytosanitary challenges such as Fusarium wilt, caused by fungi of the genus Fusarium, which leads to vascular browning, root necrosis, and dieback of the aerial parts. Conventional management includes the elimination of infected plants and the use of healthy seedlings. However, these strategies present limitations. As an alternative, biological control using fungi of the genus Trichoderma has gained attention due to its antagonistic activity against phytopathogens. In addition, essential oils have attracted interest because of their antifungal properties and low toxicity. This study evaluated the effects of essential oils on three isolates of the genera Trichoderma (CMO 16, CMO 48, and T221A) and two isolates of the genera Fusarium (FUS 1 and FUS 2), both individually and in combination, to investigate their potential as a strategy for the control of Fusarium wilt in olive trees. Seven essential oils were tested: lemongrass (Cymbopogon citratus), clove leaf (Syzygium aromaticum), spearmint (Mentha spicata), peppermint (Mentha piperita), oregano (Origanum vulgare), palmarosa (Cymbopogon martinii), and Piper aduncum L. (Piper), through individual growth and fungal antagonism assays. The data were subjected to analysis of variance (ANOVA) and presented as dot plots and heatmaps. The three Trichoderma isolates showed high tolerance to most essential oils, exhibiting maximum growth in the presence of lemongrass, spearmint, and peppermint oils. Fusarium growth was significantly inhibited, particularly by clove leaf and oregano essential oils at higher concentrations. The combination of Trichoderma and essential oils enhanced the suppression of Fusarium. The best results were obtained at the lowest concentrations of lemongrass, spearmint, and peppermint essential oils. These findings indicate that the combined use of Trichoderma and essential oils represents a promising and sustainable strategy for the control of Fusarium wilt in olive cultivation.
Compatibility between essential oils and Trichoderma sp. for antagonistic activity against Fusarium sp
Keywords: Biocontrole; Fusariose; Oliveira; Biocontrol; Essential oils; Fusarium wilt; Olive; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::MICROBIOLOGIA AGRICOLA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; 2. Fome Zero e Agricultura Sustentável; 12. Consumo e Produção Responsáveis